Effects of Combining Application between Palm-oil Fruit Bunch Organic Fertilizer and Synthetic Nitrogen on Cucumber Yields - Rina Perwanti Naibaho; Fahrurrozi Fahrurrozi; Hasanudin Hasanudin; Bambang Gonggo Murcitro; Kanang Setyo Hindarto; Nadrawati Nadrawati (TERRA : Journal of Land Restoration, 2019)
Cucumber is one of popular vegetables among consumers and widely cultivated by in Indonesia. Since there is an increasing concern of fertilizer costs and sustainability of land resources, the use of synthetic fertilizer must be minimized by using more organic sources, including the use of waste of fruit bunch of palm oil as compost. This experiment aimed to determine the best combination of between palm-oil fruit bunch organic fertilizer and synthetic nitrogen on cucumber yields. Treatments were consisted of (1) without palm-oil bunch organic fertilizer + without Urea, (2) without palm-oil bunch organic fertilizer + Urea 50 kg ha-1 , (3) without palm-oil bunch organic fertilizer + Urea 150 kg ha-1 , (4) without palm-oil bunch organic fertilizer + Urea 250 kg ha-1 , (5) palm-oil bunch organic fertilizer 5 tons ha-1 + without Urea, (6) organic fertilizer palm-oil bunch 5 tons ha-1 + Urea 50 kg ha-1 , (7) palm-oil bunch organic fertilizer 5 tons ha-1 + Urea 150 kg ha-1 , (8) palm-oil bunch organic fertilizer 5 tons ha-1 + Urea 250 kg ha-1 , (9) palm-oil bunch palm-oil bunch organic fertilizer 10 tons ha-1 + without Urea, (10) palm-oil bunch organic fertilizer 10 tons ha-1 + Urea 50 kg ha-1 , (10) palm-oil bunch organic fertilizer 10 tons ha-1 + Urea 150 kg ha1 , (12) palm-oil bunch organic fertilizer 10 tons ha-1 + Urea 250 kg ha-1 . Results indicated that combination application between palm-oil fruit bunch organic fertilizer and synthetic nitrogen significantly effects fruit length, fruit diameter, number of fruit planted, fruit weight per plot, number of fruit per plot and fruit weight per plot. It was concluded that the use of 10 tons ha-1 of palm-oil bunch organic fertilizer in combination with 250 kg ha-1 of Urea (P12) was the best treatment combination to increase cucumber yields.